Do Migrant Girls Always Perform Better? Differences between the Reading and Math Scores of 15-Year-Old Daughters and Sons of Migrants in PISA 2009 and Variations by Region of Origin and Country of Destination - Nils Kornder; Jaap Dronkers (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
As a follow-up of earlier analyses of the educational performance of all pupils with a migration background with Programme for International Student Assessment (PISA) waves 2003 and 2006, we analyze the differences between the educational performance of 15-year old daughters and sons of migrants from specific regions of origin countries living in different destination countries. We use the newest PISA 2009 wave. Instead of analyzing only Western countries as destination countries, we analyze the educational performance of 16,612 daughters and 16,804 sons of migrants in destination countries across Asia, Europe, Latin America, and Oceania. We distinguish 62 origin countries and 12 origin areas in 30 destination countries. We test three hypotheses: 1) The daughters of migrants from poorer, more traditional regions perform much better in reading than comparable sons of migrants from the same origin regions, while the daughters of migrants from more affluent and liberal regions perform slightly better in reading than comparable sons of migrants from the same regions. 2) Individual socioeconomic background has a stronger effect on the educational performance of daughters of migrants than on the performance of sons of migrants. 3) The performance of female native pupils has a higher influence on the performance of migrant daughters than the performance of male native pupils has on the performance of migrant sons. The first hypothesis can only partly be accepted. Female migrant pupils have both higher reading and math scores than comparable male migrant pupils, and these gender differences among migrant pupils are larger than among comparable native pupils. The additional variation in educational performance by region of origin is, however, not clearly related to the poverty or traditionalism of regions. Neither the second nor the third hypothesis can be accepted, given our results.
Keywords: 330